Penerapan Computational Thinking pada Pelajaran Matematika di Madratsah Ibtidaiyah Nurul Islam Sekarbela Mataram - Apriani Apriani; Ismarmiaty Ismarmiaty; Dyah Susilowati; Kartarina Kartarina; Wiya Suktiningsih (LPPM Universitas Bumigora, 2021)
This service activity aims to contribute knowledge to teachers to be able to understand and implement computational thinking in the subjects they are taught. The lack of trained personnel and the lack of understanding in implementing computational thinking gives the Bebras Bureau the opportunity to contribute. This is in line with Mendikbud's desire to implement computational thinking in the children's education curriculum as a provision for more innovative learning to answer the needs of the industrial era 4.0. Computational thinking is the process of thinking in formulating a problem and its solution so that the solution can be represented in a form that can be executed by an information-processing agent. The implementation of the service was carried out on the Mathematics subject teacher at Nurul Islam Mataram Elementary School. The implementation stages consist of planning, preparation, socialization, training, and evaluation. The results of the evaluation showed that most of the teacher participants agreed to apply the results of the training to students and most participants agreed to join the follow-up programs from Bebras. It is hoped that this activity can run continuously and be supported positively by the parties involved.